Finite element analysis of 3D reinforced concrete frame using ANSYS - Muhammad Adib, Embong (2015)
In this research, 3D reinforced concrete frame structure is analyzed by using Probabilistic Method with ANSYS and checked by Finite Element Method and Eurocode 3. This analysis is to determine the behavior of the reinforced concrete frame and to study about the probabilistic response analysis and input sensitivities of the reinforced concrete frame. Nowadays, reinforced concrete frame is widely used in many high rise building construction include shopping mall, condominium, apartment and tower. The material used in this analysis is 30N/mm2 of concrete and 500N/mm2 of reinforced steel bar. The material and geometry of the reinforced concrete frame was satisfied for this research since it passed all the design criteria in designing for axial bending, shear & torsion and cracking. The numerical results show very good agreement with manual calculation results. From the results of simulation, we get to know the real behavior of the structure under the applied loads. In probabilistic analysis, we get the results of cumulative distribution function, histogram plot, sensitivity plot and simple history plot by 10000 times of simulation for any input and output